A Study on Behaviour of Cylindrical and Hyperbolic Paraboloid Type of Shell Roofs for Fixed and hinged Boundary Conditions - V Patil, Sachin; R Suresh, Y (International Journal of Engineering and Technology, 2018)
Concrete shell roofs exhibit high structural efficiency, thus can be constructed very thin. Because of their light weight nature, the shape of shell roof is typically established so that it performs optimally under gravity loads and Carry load to foundation mainly through membrane action over shell surface. The behaviour of shell roof is studied by performing linear static analysis by varying geometrical parameters and boundary conditions. Behaviour is studied in terms of displacement, and stiffnesscan be predicted.Â Â